APLIKASI MONITORING KEBERSIHAN SARANA DAN PRASARANA KAMPUS BERBASIS WEB MENGGUNAKAN TEKNIK RESPONSIF PADA ANDROID - Nuryani, Ely; Romdoni, Mochamad Yusuf (Jurnal Sistem Informasi, 2020)
Campus facilities and infrastructure are assets that used to support teaching and learning activities. Campus facilities and infrastructure are not only to use but its need to be kept clean. But in reality, campus facilities and infrastructure are often neglected in terms of cleanliness. The neglect of the cleanliness is caused by several things such as lack of supervision by the facilities and infrastructure department, difficulty in checking facilities and infrastructure due to their large number and located in a fairly large area, and limited cleaning personnel. To deal with this problem, a campus facility and infrastructure cleanliness monitoring application was designed. In designing this application using the System Development Life Cycle (SDLC) method, the stages are planning, analysis, design, implementation, testing, and operation. The application is a web-based responsive application with Android operating system platform. Responsiveness is one of the techniques used in developing web-based applications so that the application is able to be run and adjusted to the screen of the device. The programming languages ​​used are PHP and MySQL combined with CSS framework, namely bootstrap. The application built is equipped with a feedback facility that can be used by the leader in the form of comments and also rating on each cleanliness report from each unit and location. The comments and ratings given by this leader to increase a moral impact on the person in charge of cleanliness directly. In the end, this application is designed to help facilities and infrastructure department and leaders in monitoring the cleanliness of the facilities so that they can improve the quality of the cleanliness of campus infrastructure and facilitate and also smoothen the process of teaching and learning activities